Creación de un centro de arte para menores de edad con capacidades diferentes, administrado por el departamento de dirección de desarrollo humano e inclusión social del Gobierno Autónomo Descentralizado Municipal del cantón el Empalme año 2014 - Rosado Sánchez, Verónica Catalina (2014)
The creation of an arts center for children with disabilities, the Canton the splice will be under the implementation of the decentralized autonomous Municipal Government of the Canton The splice 2014, is a project will provide a social service to the citizens of this canton, which possess some type of disability, which will allow for the development of their skills to a higher level, through singing, music, theater or dance. He understood the preliminary phase of the thesis, chapter I, with the diagnosis of problematization, which has formulated a problem, in the absence of an Art Center, as well also be justified because it has importance, in the personal development and psychomotor of children with disabilities, this chapter also allowed the enunciation of the objectives, seeks to establish how they fare and identify their needs, and the hypothesis arises in relation to improve their quality of life.All foundations, theoretical, conceptual and legal, in Chapter II, this book authors, as well as important information websites, MIESS and others who formulated scientific theories were consulted, the foundation legal, I got it from the Constitution of the Republic, Organic, Disabilities Act Code of Childhood and Adolescence, National Development Plan, for the good life, Ordinance disabilities Elimination of Architectural Barriers and Urbanísticas Canton El Empalme. Chapter III, the research demonstrates the types of methods, techniques and sources that participated in the survey conducted for this thesis. Obtaining practical results are considered by tabulating the survey, analysis, interviews, and development studies, technical, economic and financial, which proved the social benefits that this would bring to the citizens of Canton The Empalme and their families minors who have disabilities, all this in Chapter IV,It is concluded in Chapter V, which is executable and socialization of the thesis, the hypothesis is rejected because it has not yet come to meet recommended. Improving the quality of life, thanks to the creation of the center